Factores laborales y estrés en las enfermeras del servicio de cuidados intensivos e intermedios - Soles Haro, Azucena Linda (2019)
The following quantitative, descriptive - correlational study was carried out with the objective of determining the relationship between labor factors of work content, physical and organizational conditions with the level of stress in Nurses of the Intensive and Intermediate Care Services of the adult Víctor Lazarte Echegaray Hospital. The sample consisted of 25 nurses. For data collection, two instruments with a Likert scale were used, the first instrument to determine labor factors and the second instrument to measure the Stress Level in nurses. The information collected through the described instruments was entered and processed in the statistical program IBM SPSS STATISTICS Version 25. To determine the type of relationship between the variables, the tau B test was used, considering that there is sufficient evidence of statistical significance if the probability of being wrong is less than or equal to 5 percent (p≤0.05). Concluding that, 56.0% of nurses in the work content factor present a medium level. 52.0% of nurses in the organizational factor show a medium level and 60.0% of nurses in the physical environment factor show a low level. 76.0% of nurses have a medium level of stress. There is no statistically significant relationship between the work content factor, organizational factors, physical environment factor with the level of stress in intensive care unit nurses. (p = 0.0.736). (p = 0.936) and (p = 0.945).